Asymmetric Total Synthesis of Cephanolide A. (15th September 2020) - Zhang, Hongyuan; He, Haibing; Gao, Shuanhu
Abstract: The first asymmetric total synthesis of cephanolide A, a complex hexacyclic C18 dinorditerpenoid from cephalotaxus sinensis, was achieved. The synthesis features a convergent strategy, which provides a flexible approach to prepare the biogenetically cephalotaxus diterpenoids and structurally related derivatives for biological studies. A mild intramolecular Prins cyclization was developed to construct the central hexahydrofluorenol skeleton (A‐B‐C ring), which relies on the originally proposed hydroacylation strategy. A remote hydroxy group directed hydrogenation was applied to stereospecifically reduce the tetra‐substituted enone unit. A sequence of ring forming steps, including lactonization, cation mediated etherification and Friedel–Crafts cyclization, was efficiently utilized to forge the cage‐like skeleton. Abstract : The asymmetric total synthesis of cephanolide A, a complex hexacyclic C18 dinorditerpenoid from cephalotaxus sinensis, is described. Key features are the stereo‐controlled formation of the contiguous stereogenic centers on C ring, a Prins cyclization (B ring), a cation‐mediated etherification (E ring), and an intramolecular Friedel–Crafts reaction (D ring).